Current hotspot and study trend of innate immunity in COVID-19: a bibliometric analysis from 2020 to 2022 - Lai, Ping; Xu, Shuquan; Xue, Jin-hua; Zhang, Hong-zhou; Zhong, Yi-ming; Liao, Yong-ling (Frontiers in Immunology, 2023)
Background: Since coronavirus disease 2019 (COVID-19) has spread throughout the world, many studies on innate immunity in COVID-19 have been published, and great progress has been achieved, while bibliometric analysis on hotspots and research trends in this field remains lacking. Methods: On 17 November 2022, articles and reviews on innate immunity in COVID-19 were recruited from the Web of Science Core Collection (WoSCC) database after papers irrelevant to COVID-19 were further excluded. The number of annual publications and average citations per paper were analyzed by Microsoft Excel. Bibliometric analysis and visualization of the most prolific contributors and hotspots in the field were performed by VOSviewer and CtieSpace software. Results: 1,280 publications met the search strategy on innate immunity in COVID-19 and were published from 1 January 2020 to 31 October 2022. 913 articles and reviews were included in the final analysis. The USA owned the highest number of publications (Np) at 276, number of citations without self-citations (Nc) at 7,085, as well as H-index of 42, which contributed 30.23% of the total publications, followed by China (Np:135, Nc: 4,798, and H-index:23) with 14.79% contribution. Regarding Np for authors, Netea, Mihai G. (Np:7) from the Netherlands was the most productive author, followed by Joosten, Leo A. B. (Np:6) and Lu, Kuo-Cheng (Np:6). The Udice French Research Universities had the most publications (Np:31, Nc:2,071, H-index:13), with average citation number (ACN) at 67. The journal Frontiers in Immunology possessed the most publications (Np:89, Nc:1,097, ACN:12.52). "Evasion" (strength 1.76, 2021-2202), "neutralizing antibody" (strength 1.76, 2021-2202), "messenger RNA" (strength 1.76, 2021-2202), "mitochondrial DNA" (strength 1.51, 2021-2202), “respiratory infection” (strength1.51, 2021-2202), and "toll-like receptors" (strength 1.51, 2021-2022) were the emerging keywords in this field. Conclusion: Study on innate immunity in COVID-19 is a hot topic. The USA was the most productive and influential country in this field, followed by China. The journal with the most publications was Frontiers in Immunology. "messenger RNA", "mitochondrial DNA", and "toll-like receptors" are the current hotspots and potential targets in future research.